A Scientific Theory of the Development of Meditation in Practicing Individuals: Patañjali’s Yoga, Developmental Psychology, and Neurobiology - Dale, Edward James (Sophia, 2014)
This article considers the psychology of meditation and other introverted forms of mystical development from a neo-Piagetian perspective, which has commonalities with biogenetic structuralist and neurotheological approaches. Evidence is found that lines of meditative development unfold through Patañjali’s stages at different rates in an echo of the unfolding of lines of cognitive development through Piaget’s stages at different rates. Similar factors predicting the degree of independence of development apply to both conventional cognitive and meditative contents. As the same brain and the same nervous system are involved in both cognitive developmental psychology and meditation there are likely to be commonalities between conventional psychological and transpersonal development. Neo-Piagetian transpersonal psychology predicts a variable landscape of spiritual development across traditions and individuals, in line with variability in the cultural learning environment.